Rheumatoid Arthritis Related Interstitial Lung Disease: Patterns in High-Resolution Computed Tomography - Ranabhat, Nawaraj; Poudel, Bipin; Paudyal, Buddhi Prasad; Bhattarai, Rakshya; Gautam, Mahesh; Chapagain, Ashok; Aryal, Rakshya (Journal of Nobel Medical College, 2025)
Background: Rheumatoid arthritis is a systemic inflammatory disease with extra-articular manifestations, among which interstitial lung disease is one of the most severe, contributing significantly to morbidity and mortality. Early detection of RA-associated ILD is critical, and high-resolution computed tomography has emerged as a highly sensitive diagnostic tool. Materials and Methods: A retrospective, cross-sectional analytical study was conducted at the Department of Radiology, Patan Academy of Health Sciences, from June 2021 to June 2024. High Resolution Computed Topography (HRCT) scans of 400 patients diagnosed with Rheumatoid Arthritis were reviewed for interstitial lung abnormalities. Patterns were analyzed based on lung zones and laterality. Results: Pulmonary abnormalities suggestive of Rheumatoid Arthritis - Interstitial Lung Disease were present in 78% of the patients. The most frequent High Resolution Computed Topography (HRCT) findings were ground glass opacities (39.1%), honeycombing (19.9%), traction bronchiectasis (16.6%), and parenchymal bands (14.8%). UIP (43.75%) and NSIP (30.25%) were the predominant diagnostic patterns. Right lung and lower zone involvement were more common. Nodules, tree-in-bud appearance, and crazy-paving were notably absent. Conclusion: The study found a high prevalence of interstitial lung disease (ILD) among rheumatoid arthritis (RA) patients, with usual interstitial pneumonia (UIP) and nonspecific interstitial pneumonia (NSIP) as the dominant High Resolution Computed Topography (HRCT) patterns. Ground glass opacities and fibrotic changes, especially in the lower lung zones, were the most common radiologic features. Routine High Resolution Computed Topography screening in Rheumatoid Arthritis patients can facilitate early diagnosis of Interstitial Lung Disease and improve clinical outcomes, particularly in resource-limited settings.